AMBIENT AMMONIA STRESS ON CERTAIN DETOXIFYING ENZYMES IN KIDNEY TISSUES OF FISH, CYPRINUS CARPIO - P. HARI; P.NEERAJA (International Journal of Pharma and Bio Sciences, 2012)
Presently, aquatic pollution by ammonium compounds, due to their large scale production and the indiscriminate usage for the agriculture and aquaculture farms, has earned an important place among the environmental pollutants. Industrial effluents, bio degradation of waste products and food remains also contribute for the formation of considerable quantity of ammonia in the environment. Ammonia when present in higher concentration is toxic to living animals and produces several biochemical and physiological changes at cellular level. In view of these some of the important physiological and biochemical events occurring under ammonia stress in the animal, Fish Cyprinus carpio is taken for the present study. Animal weighting 120±10 g and 17±2 cm length are exposed to 4 ppm of ammonia solution for 7days. In order to understand the effect of chronic ammonia stress on the detoxification aspect of the kidney tissue, activity levels of arginase,Glutathioneperaxidase(GPx),Glutathione–s-ransferase(GST),Glutaminesynthetase(GSH), Glutamate dehydrogenase (GDH),Xanthine Oxidase (XOD),Catalase (CAT), Superoxide dismutase(SOD) enzyme levels were estimated in the kidney tissue of the animal. Increased activity levels in Arginase, GPx, GST,GSH, GDH , XOD, CAT and SOD enzyme levels was observed on prolonged ammonia exposure.